Adaptation of Independent Learning Curriculum by Elementary School Teachers: Case Study in the Indonesia–Malaysia Border Region - Okta, Setyo Luthfi; Putra, Deva (Research Collaboration Community (RCC), 2025)
This study examines the process of adapting the Merdeka Curriculum by elementary school teachers in the Indonesia-Malaysia border area, especially in Kapuas Hulu Regency, West Kalimantan. Using a descriptive qualitative approach and case study method, this study aims to explore adaptation strategies, implementation challenges, and leadership roles in implementing the new curriculum in the 3T (underdeveloped, outermost, and frontier) areas. Data were collected through direct observation, in-depth interviews with six class teachers and one principal, and analysis of learning documentation. The results of the study indicate that teachers' understanding of the basic concepts of the Merdeka Curriculum such as differentiated learning and the Pancasila Student Profile has not been accompanied by adequate technical skills in its implementation. Teachers developed adaptation strategies in the form of simplifying materials, using local content such as folklore and traditional games, and informal collaboration in developing learning. The main challenges to implementation include limited infrastructure (45%), minimal teacher training (30%), and conventional learning culture (25%). The role of the principal as a facilitator and coordinator is very significant in overcoming implementation gaps. This study concludes that the adaptation of the Merdeka Curriculum in border areas requires a flexible and contextual approach by considering local geographic, socio-economic conditions, and human resource capacity. Place-based policies and strengthening collaboration between schools, local governments, and communities are needed to realize the implementation of a just and equitable curriculum throughout Indonesia.